Modern tragedies in self-help literature, blogs and online universes: conceptions of resilience as a literary phenomenon. Issue 4 (20th February 2020) - Christensen, Louise Folker; Simonsen, Peter; Folker, Anna Paldam
Abstract : Focusing on the configuration of the relationship between fate and freedom of action, this article analyses recent self-help literature and online communities, particularly the genre that centres on the concept of resilience. The selected works and websites all address readers who suffer from depression, anxiety and stress. The article focuses on how the relationship between fate and freedom is represented in three literary figures: the reader, who is promised recovery; the narrator, who promises to save the reader from the mental illnesses; and the plot that the reader forms by his or her personal thoughts, feelings and experiences. Furthermore, fate and freedom will be analysed in a series of allegories and metaphors. We argue that each literary figure reflects a radical understanding of individual autonomy, that is, freedom of action. However, we also argue that each literary figure has a shadowy disadvantage, which activates a tragic reversal of fate. The article analyses how this self-help genre reflects a notion of tragedy in relation to mental suffering.